Pulse Signal Inverse Scattering by Perfectly Conducting Object Located near Uniform Half-Space - Sukharevsky, O. I.; Gorelyshev, S. A.; Vasilets, V. A.; Muzychenko, A. V. (Видавничий дім «Академперіодика», 2013)
Pulse Signal Inverse Scattering by Perfectly Conducting Object Located near Uniform Half-Space